LAYANAN INFORMASI PERPUSTAKAAN BERBASIS E-MAIL (Information Technology and Telematics, 2014)
AbstrakLibrary information services based on E-mail is very beneficial for the visitors, because visitors can access the information they need and want without being limited by space and time as long as they have an internet connection to access their e-mail accounts The purpose of this service is to produce a library information based on email service that allows the reader who wants to know or find the information they need online.Keywords: library, e-library, e-mail, information services.